Ampelisca mississippiana: a new species (Crustacea: Amphipoda: Gammaridea) from the Mississippi Canyon (Northern Gulf of Mexico) - Soliman, Yousria; Wicksten, M.ary (Zootaxa, 2007)
A new ampeliscid species (Amphipoda, Gammaridea) was recovered in high densities from a depth of about 480 m at the Mississippi Canyon (28 32' N, 89 49' W). Ampelisca mississippiana is described and illustrated based on specimens collected from the head of the canyon, where the species formed an ampeliscid mat with average densities of 12,000 ind. m -2 . Ampelisca mississippiana resembles A. pugetica Stimpson, 1864, and A. mexicana Barnard, 1954a, but differs in the shape of the head, absence of corneal lenses, relative lengths of antennae 1 and 2, shape of the segments of pereopods 7, and shape of the carina of the urosome. The new species also resembles Ampelisca uncinata Chevreux, 1887, but differs in the shape of the head, the dorsal carina of pleon segment 4, features of some segments of pereopod 7, the second uropod and the mouthparts.